Neural networks art: solving problems with multiple solutions and new teaching algorithm - Dmitrienko, V. D.; Zakovorotnyi, A.; Leonov, S. Yu.; Khavina, I. P. (My University, 2014)
A new discrete neural networks adaptive resonance theory (ART), which allows solving problems with multiple solutions, is developed. New algorithms neural networks teaching ART to prevent degradation and reproduction classes at training noisy input data is developed. Proposed learning algorithms discrete ART networks, allowing obtaining different classification methods of input.
Keywords: degradation of breeding classes; learning algorithms; neural network adaptive resonance theory; problems with multiple solutions